Visualization of the Drosophila dKeap1-CncC interaction on chromatin illumines cooperative, xenobiotic-specific gene activation - Deng, Huai (The Company of Biologists, 2014)
Interactions among transcription factors control their physiological functions by regulating their binding specificities and transcriptional activities. We implement a strategy to visualize directly the genomic loci that are bound by multi-protein complexes in single cells in Drosophila. This method is based on bimolecular fluorescence complementation (BiFC) analysis of protein interactions on polytene chromosomes. Drosophila Keap1 (dKeap1)-CncC complexes localized to the nucleus and bound chromatin loci that were not bound preferentially by dKeap1 or CncC when they were expressed separately. dKeap1 and CncC binding at these loci was enhanced by phenobarbital, but not by tert-butylhydroquinone (tBHQ) or paraquat. Endogenous dKeap1 and CncC activated transcription of the Jheh (Jheh1, Jheh2, Jheh3) and dKeap1 genes at these loci, whereas CncC alone activated other xenobiotic response genes. Ectopic dKeap1 expression increased CncC binding at the Jheh and dKeap1 gene loci and activated their transcription, whereas dKeap1 inhibited CncC binding at other xenobiotic response gene loci and suppressed their transcription. The combinatorial chromatin-binding specificities and transcriptional activities of dKeap1-CncC complexes mediated the selective activation of different sets of genes by different xenobiotic compounds, in part through feed-forward activation of dKeap1 transcription.